Perceived Quality of Life and Frailty Among Older People Living in Different Settings - Vanessa Clivelaro Bertassi Panes; Magali de Lourdes Caldana; Maria José Sanches Marin; Patricia Ribeiro Mattar Damiance; Patrick Alexander Wachholz (Brazilian Society of Geriatrics and Gerontology, 2024)
OBJECTIVE: To analyze the perceived quality of life of older people living in the community and long-term care facilities, and correlate it with the presence of frailty. METHODS: This is a quantitative, analytical, cross-sectional study in which 136 older people were interviewed, half were living in the community and the other half were living in long-term care facilities. The Edmonton Frail Scale was used to identify frailty, and the World Health Organization Quality of Life - Bref (WHOQOL-BREF) and World Health Organization Quality of Life Assessment for Older Persons (WHOQOL-OLD) questionnaires were used to measure quality of life. Analysis of variance and Pearson correlation coefficients were used for intragroup analyses. RESULTS: A greater proportion of older people living in long-term care facilities were frail. Perceived quality of life was better among people living in the community, according to both questionnaires, particularly in the domains social relations, environment, and death and dying. The worst scores were observed in the autonomy domain, particularly among older people living in long-term care facilities. In the majority of domains, older people with frailty had worse perceived quality of life scores. CONCLUSIONS: The absence of frailty favors a better perception of the quality-of-life domains, as does living in the community.